NIMG-53. POST-SURGICAL, RESIDUAL ENHANCING TUMOR VOLUME IS PROGNOSTIC FOR OVERALL SURVIVAL IN NEWLY DIAGNOSED GLIOBLASTOMA: EVIDENCE FROM 1, 458 PATIENTS POOLED FROM INTERNATIONAL TRIALS, SINGLE INSTITUTION DATABASES, AND MULTICENTER CONSORTIUMS. Issue 11 (6th November 2017) - Ellingson, Benjamin; Abrey, Lauren; Nelson, Sarah; Garcia, Josep; Chinot, Olivier; Saran, Frank; Nishikawa, Ryo; Henriksson, Roger; Mason, Warren; Wick, Wolfgang; Butowski, Nicholas; Ligon, Keith; et al.
Abstract: The prognostic significance of residual contrast enhancing tumor volume after initial surgery to predict OS in newly diagnosed GBM remains poorly understood and not controlled for in prospective clinical trials. In the current study we pooled imaging data in >1, 400 newly diagnosed GBM patients from international multicenter clinical trials, single institution databases, and multicenter clinical trial consortiums identify relationships between clinical parameters, MGMT methylation status, treatment, and residual enhancing tumor volume on OS. METHODS: Data from 1, 458 newly diagnosed GBM patients from 3 sources (2 for training and 1 for validation) were included in our imaging database: 1) a single institution database from UCLA (N=398; Training Set 1); 2) patients treated within the Ben and Cathy Ivy Foundation for Early Phase Clinical Trials Consortium (N=262 from 8 centers; Training Set 2); and 3) AVAglio – an international phase III trial comparing chemoradiation plus bevacizumab (N=404) vs. placebo (N=394) used as a validation set. Post-surgical, residual enhancing disease was isolated from blood products and quantified using T1 subtraction maps. Multivariate Cox regression models were used to determine influence of clinical variables, MGMT status, and residual tumor volume on OS. RESULTS: Results confirmed that post-surgical, residual enhancing tumor volume is a strong prognostic factor for OS (P<0.0001), regardless of therapy, age, and MGMT status. Pre-surgical tumor volume and extent of resection as continuous variables were not significant prognostic factors, but patients with an extent of resection greater than 98% had a significant survival advantage (P<0.01). Influence of residual non-enhancing disease and other imaging factors will also be discussed. CONCLUSION: Results support the hypotheses that post-surgical, residual contrast-enhancing disease significantly influences survival in patients with newly diagnosed glioblastoma, regardless of treatment.